Harmonic Mitigation with Active Filter in Coal Boiler Plant PT. Salim Ivomas Pratama - Widagdo, Reza Sarwo; Andriawan, Aris Heri; Tauladan, Imam Suri (Politeknik Caltex Riau, 2023)
Coal Boiler Plant at PT. Salim Ivomas Pratama is a plant for making steam, almost all activities in the cooking oil and margarine production process utilize electrical energy, such as submersible and centrifugal electric motors with controllers, computers, AC inverters, and many others which include non-linear loads. Electrical load whose correlation between voltage and current is unbalanced, this non-linear load will result in harmonic disturbances in the electric power system which causes a reduction in the service life of electrical equipment. Harmonics are defined as voltage and current frequency distortions that are not sinusoidal from pure frequencies. This study aims to determine how effective the active filter design simulated with the PSIM Software is in reducing harmonics with a non-linear load of 3 VSD connected to a 55 kW, 0.37 kW, and 7.5 kW induction motor. The results of measurements and analysis show that there are harmonics on the panel. SDP with a current harmonic value for phase R of 26.6%, phase S of 27.5%, and phase T of 25.5%, when compared with standard harmonics, all phases exceed the standard SPLN with a standard value of 20%. Then it is necessary to reduce harmonics with an active filter, after designing andsimulating it in the PSIM software the simulation results show that the current harmonics have changed for phase R by 3.3%, phase S by 4.0%, and phase T by 3,4 %. This shows that the design of the active filter is quite effective in mitigation a harmonic, to then be applied in practice at PT. Salim Ivomas Pratama in reduction the harmonics in a coal boiler plant.